2014
DOI: 10.1016/j.foodres.2014.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Pterospartum tridentatum, Gomphrena globosa and Cymbopogon citratus: A phytochemical study focused on antioxidant compounds

Abstract: Pterospartum tridentatum (L.) Willk., Gomphrena globosa L. and Cymbopogon citratus (DC) Stapf. are examples of medicinal plants that demand a more detailed characterization. Therefore, phenolic composition (e.g., phenolic acids and flavonoids) was analysed by chromatographic and mass spectrometry techniques and the antioxidant activity was also accessed through free radicals scavenging activity, reducing power and inhibition of lipid peroxidation in brain homogenates.C. citratus revealed the highest β-carotene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 51 publications
10
86
3
Order By: Relevance
“…The identification of these compounds was previously performed by authors (Roriz et al, 2014) and confirmed in this study. Four betacyanin compounds were found: gomphrenin II (P1), gomphrenin III (P2), isogomphrenin II (P3) and isogomphrenin III (P4).…”
Section: Betacyanins Analysis and Quantificationsupporting
confidence: 76%
“…The identification of these compounds was previously performed by authors (Roriz et al, 2014) and confirmed in this study. Four betacyanin compounds were found: gomphrenin II (P1), gomphrenin III (P2), isogomphrenin II (P3) and isogomphrenin III (P4).…”
Section: Betacyanins Analysis and Quantificationsupporting
confidence: 76%
“…16 Plants of this family are particularly predominant in South America, consisting of approximately 120 species, which are employed in folk medicine in the treatment of several diseases due to their biological activities, including antimicrobial, 17 antioxidant, cytotoxic, 18 and hypotensive activities, 19 and they also possess nutritive value. 20 Recent studies have focused mainly on the most common cultivar, purple globe amaranth, dealing with its phytochemical composition, 20,21 antimicrobial, antioxidant and cytotoxic activities, and cardiovascular effects, 18,22,23 as well as its medicinal benefits. 24 Nevertheless, to the best of our knowledge, other Gomphrena species are still poorly or not studied and, since the consumption data indicate that these plants are widely employed around the world for various purposes, especially their traditional use as infusions in order to treat throat disorders, hence it seems of great interest to explore their bioactive potential.…”
Section: 15mentioning
confidence: 99%
“…21 MS detection was performed in an API 3200 Qtrap (Applied Biosystems, Darmstadt, Germany) equipped with an ESI source and a triple quadrupole-ion trap mass analyser that was controlled by the Analyst 5.1 software. Zero grade air served as the nebulizer gas (30 psi) and turbo gas was used for solvent drying (400°C, 40 psi).…”
Section: Organic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies previously conducted demonstrated its hypoglycemic, hipolypidemic, anxiolytic, sedative, antioxidant and anti-inflammatory effects [1][2][3][4][5]. Some researchers have studied diverse-origin samples of lemongrass regarding their phenolic composition and antioxidant and anti-inflammatory properties [6][7][8][9]. In the past years, the phenolic composition of lemongrass infusion was described: 3-feroylquinic acid, neochlorogenic acid, chlorogenic acid, p-coumaric acid, carlinoside, isoschaftoside, isoorientin, cynaroside, veronicastroside, luteolin 7-O-neohesperidoside, kurilensin A and cassiaoccidentalin B [10].…”
Section: Introductionmentioning
confidence: 99%